DAMPAK PENGEMBANGAN PARIWISATA TERHADAP PERKEMBANGAN UMKM PADA KAWASAN WISATA DIENG - Bagus Prasetyo; Sri Suryoko (Universitas Diponegoro, 2018)
This research based by developing tourism on Dieng tourist destination areas. The tourism was developing continuously to increase visitors in tourist attractions on Dieng. On the processes of developing tourism will give impact to many people for participate to provide tourism industry, that’s with Small, and Medium Enterprise (SMEs). Developing of tourism give motivation for many people to build Micro, Small, and Medium Enterprise, this is based on tourism opportunities. The purpose of this study was to knowing how impact of developing tourism to small and medium enterprise and to analysis how the processes of development tourism give impact for micro, small and medium enterprise from income sector and business growth. Analysis of the data used in this research is descriptive analysis method. Based on the results of descriptive and analysis, so obtained the conclusion that’s developing tourism in Dieng tourist destination areas could increase of micro, small, and medium enterprise income in tourist destination areas Dieng, and was creating opportunities for many people to make new business with thought that’s development of tourism will bring in many tourist and a lot of money was shopping in tourist destination areas. This is prove that’s tourism could increase people opportunities for the business and growth the business. Advice can be given is still need improvement on developing tourism which has been done in tourist destination areas Dieng to accommodation tourist needs so many tourist who visiting and improving economy level of people. And needs help from the government to give education for businessmen to developing their product and market their product extensively